Science and technology of a transformational multifunctional ultrananocrystalline diamond (UNCDTM) coating. Issue 1 (24th January 2022) - Auciello, Orlando
Abstract: This review focuses on describing the fundamental/applied materials science and technological applications of a transformational multifunctional diamond-based material named ultrananocrytalline diamond (UNCD TM ) in film form. The UNCD TM films are synthesized using microwave plasma chemical vapor deposition (MPCVD) and hot filament chemical vapor deposition (HFCVD), via patented Ar/CH4 gas flown into air evacuated chambers, using microwave power, or hot filaments' surface, to crack CH4 molecules to generate C atoms and CHx ( x = 1, 2, 3) species, which produce chemical reactions on substrates' surfaces, producing diamond film with grain sizes in the range 3–5 nm (smallest grain size known today for any polycrystalline diamond film), providing the bases for the name UNCD. UNCD coatings exhibit a unique combination of properties, namely: (1) super high hardness and Young modulus, similar to the crystal gem of diamond; (2) lowest coefficient of friction compared to other diamond or diamond-like coatings; (3) no mechanical surface wear; (4) highest resistance to chemical attach by any corrosive fluid; (5) only diamond film exhibiting electrical conductivity via Nitrogen inserted in grain boundaries, binding to C atoms and providing electrons for electrical conduction, or B atoms substituting C atoms in the diamond lattice, providing electrons to the conduction band; and (6) best biocompatibility, since UNCD coatings are formed by C atoms (element of life in human DNA, cells/molecules). The UNCD films' properties provide unique multifunctionalities, enabling new generations of industrial, electronic, high-tech, and implantable medical devices/prostheses, enabling substantial improvement in the way and quality of life of people worldwide.